2022
DOI: 10.1108/ijaim-08-2022-0178
|View full text |Cite
|
Sign up to set email alerts
|

The key audit matters and the audit cost: does governance matter?

Abstract: Purpose This paper aims to investigate the relationship between key audit matters (KAMs) and audit costs and whether board size and independence affect this relationship. Furthermore, this paper examines the moderating effect of corporate governance on the relationship between KAMs and audit costs. Design/methodology/approach The authors hypothesise that disclosing more KAMs in the audit report is positively associated with audit costs because of the greater effort. The agency theory suggests that firms with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 74 publications
2
22
0
3
Order By: Relevance
“…Zhang and Shailer (2021) also documented an increase in audit fees in the UK following the adoption of KAMs reporting. While Kend and Nguyen (2022) documented increases in audit efforts and auditors' working hours after the introduction of KAMs in Australia, Elmarzouky et al (2022) reported an increase in audit fees due to KAMs reporting in the context of UK. Our findings suggest that APs perceive that the statutory audit in Bangladesh is underpriced and the increase in audit efforts due to KAMs reporting requirements will further dis-align the relationship between audit efforts and fees, thus creating a paradoxical situation: RQ4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Shailer (2021) also documented an increase in audit fees in the UK following the adoption of KAMs reporting. While Kend and Nguyen (2022) documented increases in audit efforts and auditors' working hours after the introduction of KAMs in Australia, Elmarzouky et al (2022) reported an increase in audit fees due to KAMs reporting in the context of UK. Our findings suggest that APs perceive that the statutory audit in Bangladesh is underpriced and the increase in audit efforts due to KAMs reporting requirements will further dis-align the relationship between audit efforts and fees, thus creating a paradoxical situation: RQ4.…”
Section: Resultsmentioning
confidence: 99%
“…Our study makes the following contributions. Firstly, early studies examined the effect of KAMs reporting on accrual qualities, audit fees (Gutierrez et al , 2018; Lennox et al , 2023), audit report lags (Elmarzouky et al , 2022) and audit efforts (Nguyen and Kend, 2021). We examine the stakeholders’ perceptions of the effect of KAMs reporting on audit quality and report transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, future studies could examine the impact of overlapping AC directorships on different types of voluntary disclosure, such as sustainability disclosure, as governance and sustainability remain open dialogues among stakeholders (Alkaraan, 2021(Alkaraan, , 2022. Recent research explores different types of voluntary disclosures, such as Covid-related disclosure (Elmarzouky et al, 2021), key audit matter disclosure (Elmarzouky et al, 2022a(Elmarzouky et al, , 2022b(Elmarzouky et al, , 2022c, sustainable development goals disclosure (Al Lawati and Hussainey, 2022b), and industry 4 technologies-related disclosures (Alkaraan et al, 2022(Alkaraan et al, , 2023bHussainey et al, 2022). Further research could examine the impact of different types of AC overlap on these types of disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…The narrative of financial statements as a joint product of a company and the auditor (Elmarzouky et al, 2022b(Elmarzouky et al, , 2023bDeFond and Zhang, 2014), while true, often leads to an oversimplification of the complexity and dynamics of the auditing process. Restatements indeed imply a deficiency in transparency, completeness and audit quality of the previously issued financial statements (Newton et al, 2013), but it also puts auditors under unfair scrutiny and assumes a simplistic view of the audit process.…”
Section: Literature Review and Hypotheses Development 21 Restatements...mentioning
confidence: 99%
“…To overcome this limitation, researchers often combine measures of audit inputs and outputs. The most commonly used input measure is auditor size (Elmarzouky et al, 2023a;Stice et al, 2022;Francies et al, 2013), while output measures typically include accrual models and restatements (Aobdia, 2019). Despite its importance, limited research has been done on audit quality in emerging markets, particularly JEL classification -M42 Audit(or) type and audit quality in Egypt.…”
Section: Introductionmentioning
confidence: 99%